Three-dimensional network porous structure phenolic aldehyde-sodium alginate composite carbon material as well as preparation method and application thereof

The integration of phenol-formaldehyde resin with sodium alginate in a sol-gel process forms a three-dimensional network structure for supercapacitor electrodes, addressing conductivity and surface area limitations, resulting in cost-effective and high-performance supercapacitor materials with enhanced energy and power density.

CN119724955APending Publication Date: 2025-03-28SHANDONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202411797032.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Current supercapacitor electrode materials face challenges such as low conductivity and limited effective surface area due to single carbon materials, leading to high production costs and complexity in obtaining high-purity multi-porous carbon from bio-based sources, hindering commercialization.

Method used

A three-dimensional network structure is created by combining phenol-formaldehyde resin with sodium alginate, using a sol-gel process to form a semi-interpenetrating network, which enhances the pore structure and surface area of the carbon material, eliminating the need for ion removal steps and simplifying the production process.

Benefits of technology

The resulting material exhibits high surface area, high capacitance, and long cycle stability, reducing production costs and enabling high energy and power density in supercapacitors with improved performance and scalability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177014740000051
    Figure BDA0005177014740000051
  • Figure HDA0005177014750000011
    Figure HDA0005177014750000011
  • Figure HDA0005177014750000021
    Figure HDA0005177014750000021
Patent Text Reader

Abstract

The invention relates to a phenolic aldehyde-sodium alginate composite carbon material with a three-dimensional network porous structure as well as a preparation method and application of the phenolic aldehyde-sodium alginate composite carbon material. Cheap phenol and formaldehyde are subjected to addition polycondensation, the addition polycondensation reaction time is controlled, phenolic resin is prepared, the phenolic resin and sodium alginate are mixed, a phenolic resin polymer can be uniformly dispersed in sodium alginate hydrogel, then a cross-linking agent solution is added, a semi-interpenetrating network structure is formed, and the cross-linked sodium alginate hydrogel is prepared. The preparation method has the advantages that the flexibility and the controllability are high, the obtained carbon material has high specific surface area, high specific capacitance and high cycle stability, and a new preparation thought and a new material choice are provided for preparing efficient and clean supercapacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technology of the present invention belongs to the technical field of advanced electrode material preparation, and specifically relates to a three-dimensional network porous structure phenolic formaldehyde-sodium alginate composite carbon material and its preparation method and application. Background Art

[0002] In the context of the continuous development of technology in today's society, the demand for better energy storage devices and systems is becoming increasingly urgent. As an important energy storage device, supercapacitors have many advantages such as high power density, excellent charging / discharging performance, low maintenance cost, safe operation, strong adaptability, good stability, good temperature characteristics, energy saving and environmental friendliness. The energy density is higher than that of traditional capacitors, and the power density is higher than that of batteries. The performance of supercapacitors is determined by superelectrode materials. Carbon materials are more commonly used in supercapacitor electrode materials than conductive polymers and metal oxides. Single carbon materials usually have disadvantages such as poor conductivity and low effective specific surface area. In order to overcome these problems, scientific researchers continue to explore new carbon materials and their composite structures, and are committed to developing advanced electrode materials that can meet the requirements of high energy density, high power density and long cycle life. Therefore, the study of supercapacitor electrode materials has become a research hotspot in the field of supercapacitors.

[0003] The porous carbon currently used is mainly prepared by high-temperature carbonization and chemical activation of biomass carbon sources such as rice husks, coconut shells, and apricot shells. + Mg 2+ , Ca 2+ Plasma needs to be purified to obtain high-purity porous carbon materials, which leads to complex processes, high preparation costs, and difficulty in commercial application.

[0004] Therefore, seeking low-cost, impurity-free new carbon materials is of great significance to reducing the cost of supercapacitors and promoting their commercial application. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a three-dimensional network porous structure phenolic formaldehyde-sodium alginate composite carbon material and a preparation method and application thereof.

[0006] The present invention adopts cheap phenol and formaldehyde for addition polycondensation, controls the addition polycondensation reaction time, prepares phenolic resin, mixes phenolic resin with sodium alginate, and the phenolic resin polymer can be evenly dispersed in the sodium alginate hydrogel, and then adds a crosslinking agent solution to form a semi-interpenetrating network structure, increases active sites, thereby optimizing the pore structure of the electrode material, and finally forms a three-dimensional network porous structure. The obtained composite carbon material has a large specific surface area, high specific capacitance and high cycle stability, as well as high controllability and strong expansibility.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The preparation method of the three-dimensional network porous structure phenolic-sodium alginate composite carbon material comprises the following steps:

[0009] (1) mixing phenol and sodium hydroxide uniformly, adding formaldehyde solution dropwise to carry out addition polycondensation reaction to obtain a thermosetting phenolic resin;

[0010] (2) mixing the thermosetting phenolic resin obtained in step (1) with a sodium alginate solution, adding a crosslinking agent solution, forming a semi-interpenetrating network structure using a sodium alginate sol-gel method, stirring, filtering, and drying to obtain phenolic resin-sodium alginate composite material particles;

[0011] (3) Pre-oxidizing, carbonizing, activating, washing and drying the phenolic resin-sodium alginate composite material particles of step (2) to obtain a three-dimensional network porous carbon structure.

[0012] Preferably according to the present invention, in step (1), the mass concentration of the formaldehyde solution is 30-40wt%.

[0013] Further preferably, in step (1), the mass concentration of the formaldehyde solution is 37 wt %.

[0014] Preferably, according to the present invention, in step (1), the mass ratio of phenol, sodium hydroxide and formaldehyde solution is 25:(5-8):(35-45).

[0015] Preferably, according to the present invention, in step (1), the addition polycondensation reaction temperature is 90-100° C., and the reaction time is 140-160 min.

[0016] Further preferably, in step (1), the addition polycondensation reaction temperature is 95° C. and the reaction time is 150 min.

[0017] The invention controls the addition polycondensation reaction time, and the prepared phenolic resin polymer can be more evenly dispersed in the sodium alginate hydrogel. If the reaction time is too long or too short, the obtained phenolic resin polymer is easy to agglomerate in the sodium alginate hydrogel.

[0018] Preferably according to the present invention, in step (2), the mass concentration of the sodium alginate solution is 1-3 wt %.

[0019] Further preferably, in step (2), the mass concentration of the sodium alginate solution is 1.5 wt %.

[0020] Preferably according to the present invention, in step (2), the mass ratio of the thermosetting phenolic resin to the sodium alginate solution is 1:(4-8).

[0021] Further preferably, in step (2), the mass ratio of the thermosetting phenolic resin to the sodium alginate solution is 1:6.

[0022] Preferably according to the present invention, in step (2), the cross-linking agent solution is a 0.3-0.5M CaCl2 solution.

[0023] Preferably, according to the present invention, in step (2), the amount of cross-linking agent solution added is until a phenolic resin-sodium alginate hydrogel is formed.

[0024] Preferably, according to the present invention, in step (2), the stirring time is 24 hours, and the drying is carried out at room temperature for 72 hours.

[0025] Preferably according to the present invention, in step (3), the pre-oxidation temperature is 160-200° C., and the pre-oxidation time is 4 hours.

[0026] Further preferably, in step (3), the pre-oxidation temperature is 180° C. and the pre-oxidation time is 4 hours.

[0027] Preferably, in step (3), the carbonization step is as follows: heating the obtained carbon material to 500-700° C. at a heating rate of 5-10° C. / min, and keeping the temperature for 0.5-2 h.

[0028] Further preferably, in step (3), the carbonization step is: heating the obtained carbon material to 600° C. at a rate of 10° C. / min and keeping the temperature for 1 hour.

[0029] Preferably according to the present invention, in step (3), the activation step is: mixing the obtained carbon material with saturated KOH in a mass ratio of 1:4, heating and drying at 70°C in a vacuum oven, heating to 350°C at a heating rate of 2°C / min and keeping warm for 0.5h, and then heating to 800°C at a heating rate of 10°C / min and keeping warm for 1h.

[0030] According to the preferred embodiment of the present invention, in step (3), the washing step is: washing with 5M HCl and deionized water to remove Ca in the carbon. 2+ .

[0031] A three-dimensional network porous structure phenolic formaldehyde-sodium alginate composite carbon material is prepared by adopting the above preparation method.

[0032] The above three-dimensional network porous structure phenolic formaldehyde-sodium alginate composite carbon material is used as a supercapacitor electrode material.

[0033] The technical features and beneficial effects of the present invention are as follows:

[0034] 1. The present invention adopts cheap phenol and formaldehyde for addition polycondensation, controls the addition polycondensation reaction time, and the obtained phenolic resin polymer can be uniformly dispersed in the sodium alginate hydrogel, and then a cross-linking agent solution is added to form a semi-interpenetrating network structure, which increases the active sites, thereby optimizing the pore structure of the electrode material and finally forming a three-dimensional network porous structure, which increases a large number of mesopores for the material, effectively increases the fast channel for ion transport, and significantly improves the utilization efficiency of the specific surface area, thereby improving the energy density and power density of the supercapacitor.

[0035] 2. The present invention has high controllability and strong expansibility. By controlling the addition condensation reaction time, a semi-interpenetrating network structure is formed by a sol-gel method. The phenolic resin-sodium alginate composite porous carbon material with a three-dimensional network porous structure prepared by the present invention has a high specific surface area, high specific capacitance and high cycle stability. The present invention provides a new preparation idea and material selection for the preparation of efficient and clean supercapacitors.

[0036] 3. The three-dimensional network porous structure phenolic-sodium alginate composite carbon material of the present invention is used for supercapacitor electrode materials, and exhibits ideal double-layer capacitor behavior, excellent rate performance, high specific capacitance and high cycle stability in the field of supercapacitors, providing a valuable reference for high-performance supercapacitor electrode materials.

[0037] 4. The cross-linking agent solution CaCl2 solution of the present invention has the advantages of being non-toxic, non-corrosive and having a neutral pH value, thereby preventing the acidity and alkalinity of the cross-linking agent from affecting the shrinkage and expansion of the sodium alginate molecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The three-dimensional network porous structure phenolic-sodium alginate composite carbon materials prepared in Example 1 and Comparative Examples 1 to 3 are SEM images; a) and b) are SEM images of sample PF-SA-95-120; c) and d) are SEM images of sample PF-SA-95-150; e) and f) are SEM images of sample PF-SA-95-180; g) and h) are SEM images of sample PF-SA-95-240;

[0039] Figure 2 The adsorption curve and pore size distribution curve of the three-dimensional network porous structure phenolic-sodium alginate composite carbon material obtained in Example 1 and Comparative Examples 1 to 3 are obtained by BET test;

[0040] Figure 3 The three-dimensional network porous structure phenolic-sodium alginate composite carbon material performance diagram of Example 1 of the present invention, a) is the fast diffusion capacitance ratio diagram at 200mV / s, b) is the surface-dominated capacitance contribution diagram at different scan rates, c) is the charge and discharge (GCD) curve at different current densities, d) is the charge and discharge (GCD) curve at 10A g -1Cyclic stability curves at different current densities. DETAILED DESCRIPTION

[0041] The present invention proposes a method for preparing a three-dimensional network phenolic-sodium alginate composite porous carbon material for supercapacitor electrode materials. In order to make the advantages and technical solutions of the present invention clearer and more specific, the present invention is further described below in conjunction with specific embodiments.

[0042] Example 1

[0043] The preparation method of the three-dimensional network porous structure phenolic-sodium alginate composite carbon material comprises the following steps:

[0044] (1) 25 g of phenol and 6 g of sodium hydroxide were weighed and added into a three-necked flask equipped with a reflux condenser and a stirring paddle, and then 45 g of a formaldehyde solution with a mass concentration of 37 wt % was weighed and evenly dripped into the three-necked flask using a constant pressure separatory funnel, and maintained at 95° C. for 150 min to obtain a thermosetting phenolic resin;

[0045] (2) then pouring the obtained thermosetting resin into a pre-dissolved sodium alginate solution with a mass concentration of 1.5wt% at a mass ratio of 1:6, stirring evenly, and then dropping it into a 0.4MCaCl2 solution until the soluble gel is converted into insoluble hydrogel particles, stirring in the solution for 24h, filtering and drying at room temperature for 72h, to obtain phenolic resin sodium alginate composite material particles;

[0046] (3) The carbon material was pre-oxidized in a forced air drying oven at 180°C for 4 h, and the temperature was raised to 600°C in a tube furnace at a rate of 10°C / min and kept at that temperature for 1 h.

[0047] (4) The obtained carbon material was mixed with saturated KOH in a mass ratio of 1:4, dried by vacuum heating at 70°C, heated to 350°C at a heating rate of 2°C / min and kept warm for 0.5 h, then heated to 800°C at a heating rate of 10°C / min and kept warm for 1 h. Finally, the sample was washed with 5M HCl and deionized water. The obtained sample was recorded as PF-SA-95-150, where 95 is the addition condensation reaction temperature and 150 is the phenolic resin synthesis time.

[0048] Comparative Example 1

[0049] The same preparation method as described in Example 1, except that:

[0050] In step (1), the temperature is maintained at 95° C. for 120 minutes to obtain a thermosetting phenolic resin. The remaining conditions are the same as those in Example 1, and the obtained sample is recorded as PF-SA-95-120.

[0051] Comparative Example 2

[0052] The same preparation method as described in Example 1, except that:

[0053] In step (1), the temperature is maintained at 95° C. for 180 minutes to obtain a thermosetting phenolic resin. The remaining conditions are the same as those in Example 1, and the obtained sample is recorded as PF-SA-95-180.

[0054] Comparative Example 3

[0055] The same preparation method as described in Example 1, except that:

[0056] In step (1), the temperature is maintained at 95° C. for 240 minutes to obtain a thermosetting phenolic resin. The remaining conditions are the same as those in Example 1, and the obtained sample is recorded as PF-SA-95-240.

[0057] Experimental Example 1

[0058] Figure 1 The following are scanning electron microscope images of the three-dimensional network porous structure phenolic-sodium alginate composite carbon materials obtained in Example 1 and Comparative Examples 1 to 3 of the present invention. Figure 1 It can be seen that the phenolic resin-sodium alginate composite porous carbon material presents a morphology of particle cluster accumulation. From the comparison between Example 1 and Comparative Examples 1 to 3, it can be seen that Figure 1 c) and Figure 1 d) The three-dimensional particle cluster stacking structure of Example 1 (sample: PF-SA-95-150) is the most excellent. The phenolic resin is fully and evenly dispersed in the sodium alginate hydrogel to form an excellent semi-permeable network structure, which increases the active sites. Figure 1 a) and Figure 1 b) In Comparative Example 1, the polycondensation reaction time was short, the reaction was not complete, and the degree of polymerization of the phenolic resin was low, and the sample formed was too loose; Figure 1 e) and Figure 1 h) In Comparative Examples 2 and 3, agglomeration occurs due to the long reaction time, and an ideal semi-interpenetrating network structure cannot be formed, which seriously affects the pore formation and hinders the transmission of electrons and ions inside the electrode material, thereby further reducing the electrochemical performance of the electrode material.

[0059] Experimental Example 2

[0060] Figure 2 This is a BET test graph of the three-dimensional network porous structure phenolic-sodium alginate composite carbon material obtained in Example 1 and Comparative Examples 1 to 3 of the present invention. Figure 2It can be seen that the sample PF-SA-95-150 in Example 1 exhibits typical type-IV isotherm characteristics, indicating that the sample has a rich hierarchical pore structure. In the low-pressure region (P / P0 < 0.1), the curve shows a steep upward trend, indicating that there are a large number of microporous structures in the sample. In the medium-high pressure region (0.4 < P / P0 < 1), the isotherm shows a hysteresis loop similar to type-H4, and the adsorption amount in the medium-high pressure region is high, indicating that there are also a large number of mesoporous structures in the sample.

[0061] According to the analysis of the DFT calculation results in Table 1:

[0062] Table 1

[0063]

[0064]

[0065] As can be seen from Table 1, with the increase of the reaction time, the specific surface area and total pore volume of the sample show a trend of first increasing and then decreasing. This is consistent with the results of SEM morphology observation; the sample PF-SA-95-150 in Example 1 has the highest specific surface area and total pore volume.

[0066] Experimental Example 3

[0067] Figure 3 is the performance diagram of the aqueous symmetric button-type supercapacitor assembled with the porous carbon material prepared in Example 1 of the present invention. As Figure 3 shown in a), at a high scan rate of 200 mV / s, the proportion of the rapid diffusion capacitance of PF-SA-95-150 is relatively large, indicating that the material has excellent high-rate performance. As Figure 3 shown in b), under different scan rate conditions, the surface-dominated capacitance contribution rate reaches 46% - 93%. It shows that it mainly comes from the efficient surface adsorption process. As Figure 3 shown in c), under different current densities (0.5 A g -1 ~50 A g -1 ), the GCD test shows that its capacitance is 247.65, 234.73, 225.75, 213.75, 205.35, 194.72, 176.22 Fg -1 . As shown in d), after 5000 cycles at 10 A g -1 , the initial capacitance remains at 98%, and the Coulomb efficiency is 83%, indicating outstanding cycle stability.

[0068] Example 2

[0069] The preparation method is the same as that described in Example 1, except that:

[0070] In step (1), 25 g of phenol and 5 g of sodium hydroxide are weighed and added to a three-necked flask equipped with a reflux condenser and a stirring paddle, then 40 g of a formaldehyde solution with a mass concentration of 37 wt % is weighed and evenly dripped into the three-necked flask using a constant pressure separatory funnel, and the mixture is kept at 95° C. for 150 min to obtain a thermosetting phenolic resin; the remaining conditions are the same as those in Example 1.

[0071] Example 3

[0072] The same preparation method as described in Example 1, except that:

[0073] In step (1), 25 g of phenol and 5 g of sodium hydroxide are weighed and added to a three-necked flask equipped with a reflux condenser and a stirring paddle, then 35 g of a formaldehyde solution with a mass concentration of 37 wt % is weighed and evenly dripped into the three-necked flask using a constant pressure separatory funnel, and the mixture is kept at 95° C. for 145 min to obtain a thermosetting phenolic resin; the remaining conditions are the same as those in Example 1.

[0074] Example 4

[0075] The same preparation method as described in Example 1, except that:

[0076] In step (2), the obtained thermosetting resin is poured into a pre-dissolved sodium alginate solution with a mass concentration of 1.5wt% at a mass ratio of 1:7, stirred evenly, and then dropped into a 0.3MCaCl2 solution until the soluble gel is converted into insoluble hydrogel particles, stirred in the solution for 24 hours, filtered and dried at room temperature for 72 hours to obtain phenolic resin sodium alginate composite material particles; the other conditions are the same as in Example 1.

[0077] Parts not described in the present invention can be implemented by referring to the existing technology.

[0078] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a three-dimensional network porous structure phenolic-sodium alginate composite carbon material, comprising the following steps: (1) mixing phenol and sodium hydroxide uniformly, adding formaldehyde solution dropwise to carry out addition polycondensation reaction to obtain a thermosetting phenolic resin; (2) mixing the thermosetting phenolic resin obtained in step (1) with a sodium alginate solution, adding a crosslinking agent solution, forming a semi-interpenetrating network structure using a sodium alginate sol-gel method, stirring, filtering, and drying to obtain phenolic resin-sodium alginate composite material particles; (3) Pre-oxidizing, carbonizing, activating, washing and drying the phenolic resin-sodium alginate composite material particles of step (2) to obtain a three-dimensional network porous carbon structure.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the formaldehyde solution is 30-40wt%.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of phenol, sodium hydroxide and formaldehyde solution is 25:(5-8):(35-45).

4. The preparation method according to claim 1, characterized in that: In step (1), the addition polycondensation reaction temperature is 90-100° C., and the reaction time is 140-160 min.

5. The preparation method according to claim 1, characterized in that: In step (2), the mass concentration of the sodium alginate solution is 1-3wt%, and the mass ratio of the thermosetting phenolic resin to the sodium alginate solution is 1:(4-8).

6. The preparation method according to claim 1, characterized in that: In step (2), the cross-linking agent solution is a 0.3-0.5M CaCl2 solution, the stirring time is 24 hours, and the drying is performed at room temperature for 72 hours.

7. The preparation method according to claim 1, characterized in that: In step (3), the pre-oxidation temperature is 160-200°C, the pre-oxidation time is 4 hours, and the carbonization step is: heating the obtained carbon material to 500-700°C at a heating rate of 5-10°C / min, and keeping it warm for 0.5-2 hours.

8. The preparation method according to claim 1, characterized in that: In step (3), the activation step is: mixing the obtained carbon material with saturated KOH in a mass ratio of 1:4, heating and drying at 70°C in vacuum, heating to 350°C at a heating rate of 2°C / min and keeping the temperature for 0.5h, and then heating to 800°C at a heating rate of 10°C / min and keeping the temperature for 1h. The washing step is: washing with 5M HCl and deionized water to remove Ca in the carbon. 2+ .

9. A three-dimensional network porous structure phenolic formaldehyde-sodium alginate composite carbon material prepared by the preparation method described in any one of claims 1 to 8.

10. Application of the phenolic-sodium alginate composite carbon material with a dimensional network porous structure as claimed in claim 9 as a supercapacitor electrode material.

Citation Information

Patent Citations

  • Microsphere assembled porous carbon material and preparation method and application thereof

    CN109592663A

  • High-internal phase emulsion template method for preparing porous carbon material through synergy of inner phase and outer phase

    CN110228808A

  • Aerogel film as well as preparation method and application thereof

    CN114797796A

  • Hard carbon material and preparation method thereof

    CN115332532A

  • Preparation method of phenolic resin / alginate composite porous carbon for supercapacitor electrode material

    CN118645379A

Cited By

  • Carbon material for removing organic sulfur based on ionic crosslinking-free radical copolymerization and preparation method

    CN120205095A

  • Preparation method of two-step nitrogen-doped three-dimensional network phenolic resin-based composite carbon material and application of two-step nitrogen-doped three-dimensional network phenolic resin-based composite carbon material in supercapacitor electrode

    CN121516867A

  • Preparation method of two-step nitrogen-doped three-dimensional network phenolic resin-based composite carbon material and application thereof in supercapacitor electrode

    CN121516867B